Tannins, flavonoids, and lignin levels of clitoria ternatea L legumes in different levels of urea fertilizer and harvesting age - Wardi, Wardi; Umami, Nafiatul; Kurniawati, Asih; Haryanto, Bambang; Puspito, Sigit; Hudhia Krishna, Noor (Universitas Sebelas Maret, 2023)
Objective: Clitoria ternatea L is a legume that has the potential as animal feed. This study determined to evaluate tannins, flavonoids, and lignin levels in different urea fertilizer applications and harvesting ages.Methods: This study used a split-plot design with three replications. The main plots were urea levels (0 kg/ha, 100 kg/ha, and 200 kg/ha), as subplots were harvesting ages (30, 45, and 60 days after planting (DAP)). Fresh weights of Clitoria ternatea L harvested at the ages of 30, 45 and 60 DAP were weighed and recorded. The weighed forage is put in newspapers and dried in a 55°C oven for three days to gain a constant dry weight. The dried samples were then ground using a willey mill with a sieve porosity of 1 mm. Furthermore, the sample is analyzed to determine the content of secondary metabolites. The parameters observed were tannins, flavonoids, and lignin levels. Analysis of variance (ANOVA) was used to analyze Research data, and Duncan's Multiple Range (DMRT) was used to analyze the differences between means.Results: The lowest lignin content of Clitoria ternatea L was prodiced in non-urea treatment (20.64± 2.53%), and significantly different compared to various levels of urea fertilization treatment (P<0.05). The highest tannin levels were obtained at 30 DAP harvest age (4.20±0.56%) and significantly different (P<0.05) from tannin levels at 45 and 60 DAP. The lowest flavonoid levels were obtained when the plants were harvested in 60 DAP (0.87±0.05%) and significantly different (P<0.05) compared to 30 and 45 DAP.Conclusions: The increase of urea fertilization level in Clitoria ternatea L only significantly affected lignin levels. The decrease of lignin content value is linear with the increase of harvesting age. In contrary, harvesting age of Clitoria ternatea L showed significant linear effects on tannins and flavonoids value.